Civil Liability of Businesses for The Loss of Consumer Goods Delivery Packages Through Land Transportation Services (Study at PT. Antar Lintas Sumatra Medan) - Djodie, Mohammad Effan; Jamillah; Marsella (Talenta Publisher, 2022)
Transportation is a field of activity that is very important in the life of the Indonesian people. With that the Government established a Law no. 8 of 1999 which stated that